Geohelmintiasis vs concentración de hemoglobina en escolares de la parroquia El Tambo. - Morales Carrillo, Freddy Paul (2016)
Geohelminthiasis frequently occur in developing countries, affecting individuals of all ages and sexes, considering a public health problem with a prevalence of 40 -70%, it affects mostly to children who are attending the early years of education . This work was made with the purpose of identify the type of geohelminths present in the stool, the hemoglobin values and determine whether there is a relationship with the concentration of hemoglobin in children in the school Andres Tinoco de Mercado, using a descriptive and transversal study, in which 62 samples were analyzed by direct examination; hemoglobin was determined by automated method. It was noted that the prevalence of intestinal helminths was 79.03%, highlighting the association of Trichuris trichiura and Ascaris lumbricoides (37.10%) with a predominant light intensity of infestation. It was also observed that there is a higher prevalence of women with normal hemoglobin levels (61.11%), while men showed a high prevalence with values below normal hemoglobin (68.18%). Of individuals with geohelminthiasis 97.92% had decreased hemoglobin values. These findings suggest that the school population lives in a hyperendemic area of geohelminths, consistent with the socioeconomic stratum. In addition, it was established that hemoglobin values in these schoolchildren are a factor associated with intestinal helminthiasis. Keywords: helminthiasis, hemoglobin, school,